Malignancy and mortality in people with coeliac disease: population based cohort study - West, Joe (BMJ Publishing Group Ltd., 2004)
Objective To quantify the risks of malignancy and mortality in people with coeliac disease compared with the general population. Design Population based cohort study. Setting General practice research database. Participants 4732 people with coeliac disease and 23 620 matched controls. Main outcome measures Hazard ratios for malignancy and mortality. Results Of the 4732 people with coeliac disease, 134 (2.8%) had at least one malignancy and 237 (5.0%) died. The overall hazard ratios were: for any malignancy 1.29 (95% confidence interval 1.06 to 1.55), for mortality 1.31 (1.13 to 1.51), for gastrointestinal cancer 1.85 (1.22 to 2.81), for breast cancer 0.35 (0.17 to 0.72), for lung cancer 0.34 (0.13 to 0.95), and for lymphoproliferative disease 4.80 (2.71 to 8.50). The increased risk was primarily in the first year after diagnosis, with the risk for only lymphoproliferative disease remaining significantly raised thereafter. After excluding events in the year after diagnosis, the hazard ratio for malignancy was 1.10 (0.87 to 1.39) and for mortality was 1.17 (0.98 to 1.38), giving absolute excess rates of 6 and 17 per 10 000 person years, respectively. Conclusions People with coeliac disease have modest increases in overall risks of malignancy and mortality. Most of this excess risk occurs in the year of follow up after diagnosis. People with coeliac disease also have a noticeably reduced risk of breast cancer. The mechanism of this merits further attention as it may provide insights into the cause of this common malignancy.